Condiţiile de viaţă ale populaţiei din mediul rural - Mărginean, Ioan (Calitatea Vieții, 2006)
This study presents a diagnosis of the living conditions of Romanian rural population regarding dwelling, household revenues, and consuming, concluding with the analysis of life satisfaction self-perception by subjects. The results obtained enhance a critical situation in this area (living conditions of the Romanian rural population), asking for practical intervention, in order to improve the present situation.